Contextualizing graffiti and street art in suitable museum settings: Street Art Today’s upcoming museum in Amsterdam - Di Giacomo, Giovanna (SAUC - Street Art and Urban Creativity (repository), 2020)
Overall, this essay examines the suitable settings for contextualizing graffiti and street art indoors, by introducing the upcoming museum for graffiti and street art in Amsterdam, an initiative of Street Art Today. Firstly, an overview of the project’s story, including its idealizer, location and collection is provided. Secondly, the contributions of the museum to the art form are presented. In particular, through its ambition to become a knowledge hub of graffiti and street art, the institution produces, gathers and analyses data, thus reinforcing the legitimation of these visual expressions. Finally, this article examines the expectations related to the museum’s role and its future visitors.